Quizizz and Kahoot Enhance Student Engagement and Motivation in Indonesian Language Learning at SD IT Abata Lombok - Alam, Furqon Nur; Kholid, Kholid (Lingual Journal of Language and Culture; Vol 17 No 2 (2024): Lingual: Journal of Language and Culture, 2024)
This study aims to describe the use of Quizizz and Kahoot as game-based assessment tools in teaching Indonesian at SD IT Abata Lombok during the 2023/2024 academic year. The primary focus is to explore how these applications are utilized by teachers for learning evaluation, along with the reasons and motivations behind their selection. Quizizz is employed as a formative assessment at the end of lessons, while Kahoot is used as a warm-up tool at the beginning of lessons to capture students' attention. The use of these platforms is intended to enhance student engagement and motivation, streamline the evaluation process, and create a more interactive and enjoyable learning environment. The study also aims to identify the challenges encountered during the implementation of game-based assessments, such as technical issues related to internet access and limited devices, as well as the solutions adopted by teachers to address these problems. It is expected that the findings of this study will provide further insights into the effectiveness of game-based applications in improving the quality of learning and assessment at the elementary education level.